RETHINKING THE USE OF L1 IN L2 CLASSROOM - Zulfikar Zulfikar (Universitas Islam Negeri Banda Aceh, 2018)
Using mother tongue (L1) in a foreign language (L2) classrooms is inevitable. Despite the debate over the adequacy of using L1 in the teaching of L2, this paper argues using L1 in the classroom does not hinder learning, and that L1 has a facilitating role to play in the classroom and can help L2 learning and acquisition. This paper shows that L1 is an inseparable part of language teaching, and it has several functions for both the students and teachers in English language learning and teaching. Therefore, those who believe L1 has a minimal role to play in the teaching of a foreign language are invited to think again of its role and contributions it makes to the fields of language learning and teaching.